Students as teachers: A student point of view - Heiskanen, Nelly; Käyhkö, Janina; Virtanen, Heli (LUMAT-B: International Journal on Math, Science and Technology Education, 2017)
It all started for us when we applied to lead a new course named “Sustainable development in Education” at the University of Helsinki in autumn 2014. The reward for course leaders was 5 ECTS but that did not act as a spur for us. Leading our own course sounded attractive, because the advertisement promised a multidisciplinary leader team and free hands to improve higher education pedagogy in the direction that would seem right to us. The Unit of Chemistry Teacher Education, which was also responsible for the course, selected candidates from applications to interviews. Eventually the leader team comprised of two teacher students from the Faculty of Science with different majors; Chemistry and Mathematics, together with one student from the Faculty of Biological and Environmental Sciences with the orientation of Environmental Change and Policy and Adult Education.